Pengaruh Fraud Triangle terhadap Deteksi Kecurangan Laporan Keuangan pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia Tahun Periode 2014-2017 - Ana Listya Utami; Sumarno; Baihaqi Fanani (Faculty of Economics and Business, University of Pancasakti Tegal, 2017)
The goal of this research is to analyze the effect of the fraud triangle, using external pressure, financial target, personal financial needs, ineffective monitoring and financial stability to the detection of fraudulent financial statement in banking companies that are signed up in Indonesia’s Stock Exchange within the period of 2014-2017. This research uses secondary data which are from the financial reports that are signed up in Indonesia’s Stock Exchange within the period of 2014-2017. The technique behind collecting samples to this research is purposive sampling. There are 10 banking companies that are signed up Indonesia’s Stock Exchange within the period of 2014-2017 that act samples to this research. The analysis technique used in this research is the multiple linier regression analysis. While to process the data, IBM SPSS 23.0 is being used in this research. The result this research shows that external pressure, personal financial needs, ineffective monitoring and financial stability that is proxied successively with LEVERAGE, OSHIP, BDOUT, and ACHANGE and has partial no effect on fraudulent financial statements. But financial target is proxied ROA have effect partial on fraudulent financial statement. This is due to the possibility of the large pressure from external, personal financial needs, ineffective monitoring and financial stability of the company does not affect a management to commit fraud. As for the financial targets, possibly because the magnitude of the asset that can influence someone to do fraudulent financial statement.